Virtual Reality, Metaverses and Immersive Advertising: Taxonomy for a Transmedia Mutualism - Martín Ramallal, Pablo (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
The study looks at the confluence between virtual reality (VR), metaverses and immersive advertising (IP), employing discourse analysis, case studies and a documentary review to generate a taxonomy. It highlights the role of Information and Communication Technologies in today's advertising, focusing on metaverses. It highlights how new generations adopt immersive narratives along with transmedia advertising and advertainment are effective. It is proposed that IP can enhance transmedia strategies, highlighting immersion in VR, sociability in metaverses and advantages such as engagement and personalization, although technical obstacles such as ergonomics and market fragmentation are detected.